An overview of the microstructure and mechanical properties of copper tube by SPD process. (2021) - Bodkhe, Mohan; Sharma, Sanjeev; Mourad, Abdel-Hamid I.; Sharma, Pritam Babu
Abstract: In this research, a new type of method has been proposed to deal with severe plastic deformation (SPD) with (Accumulative tube bonding expansion drawing) commonly known as the Accumulative tube bonding process. This Accumulative tube bonding expansion drawing helps in producing a (UFG) Ultrafine-grained tube in which grain size is reduced to get ultrafine material. In this research, a movable mandrel was placed inside the sample hollow tube and high fluid pressure is produced. To examined the usefulness of the proposed model a copper tube is inserted through which the microstructure and mechanical property of the proposed method is identified. For the examination, it was found that the size of the grain has decreased below 133 nm. From the outcome, it is understood that the strength increased by about 340 MPa and the yield increased by about 260 MPa after passing one test in accumulative tube bonding expansion drawing, where the initial value was found to be 70 MPa and 205 MPa respectively. The elongation of the tube reduced 40% from 50% . The massive increase in the strength is due to less ductility loss. The microhardness of the tube also increased from 60 HV to 135 HV after passing it in accumulative tube bonding expansion drawing where it showed excellent hardness.